On y-closed Dual Rickart Modules - Al-Bahrani, Bahar Hamad; Rahman, Mohammed Qader (Iraqi Journal of Science, 2021)
In this paper, we develop the work of Ghawi on close dual Rickart modules and discuss y-closed dual Rickart modules with some properties. Then, we prove that, if are y-closed simple -modues and if -y-closed is a dual Rickart module, then either Hom ( ) =0 or . Also, we study the direct sum of y-closed dual Rickart modules.